Kolaborasi Antara Sekolah dan Orang Tua dalam Mencegah Penyimpangan Remaja Melalui Pendidikan Agama Islam - Inang Inang; Irwan Irwan; Masita Masita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the forms of collaboration between schools and parents in preventing adolescent deviant behavior through Islamic Religious Education (PAI), as well as to identify the challenges and strategies implemented at SMPN 2 Sape, Bima Regency. This research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The findings indicate that the forms of collaboration include the use of communication books based on daily worship reports, regular meetings between parents and teachers, home visits, and joint religious activities. Efforts to prevent adolescent deviant behavior are carried out through contextual PAI learning, religious habituation programs such as Dhuha prayer, congregational Dzuhur prayer, Qur’an recitation, and short religious talks, as well as the implementation of an early detection system and student mentoring. The challenges encountered include parents’ limited time due to economic factors, low levels of parental education, suboptimal supervision of gadget use, and differences in religious understanding. This study concludes that the established collaboration is fairly effective but not yet optimal; therefore, strengthening communication and increasing parents’ continuous involvement are necessary.